-2000000-80000x=-42000000

Simple and best practice solution for -2000000-80000x=-42000000 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2000000-80000x=-42000000 equation:


Simplifying
-2000000 + -80000x = -42000000

Solving
-2000000 + -80000x = -42000000

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2000000' to each side of the equation.
-2000000 + 2000000 + -80000x = -42000000 + 2000000

Combine like terms: -2000000 + 2000000 = 0
0 + -80000x = -42000000 + 2000000
-80000x = -42000000 + 2000000

Combine like terms: -42000000 + 2000000 = -40000000
-80000x = -40000000

Divide each side by '-80000'.
x = 500

Simplifying
x = 500

See similar equations:

| 9x^2-28x+23=0 | | x^249=0 | | 20+17=-6+15x | | 14x-95=115 | | 1-1/4n=1/2n | | 4x+2(2x+3)=10 | | 11w=8w+21 | | 5z+9-z=13 | | (7+5n)+(1+3c)= | | 8v=56+v | | 9m-5-3m= | | 2y-20+y+y+2y-20=720 | | 17n+22=80 | | (2x)(2x)-5x=3000 | | 9u=49+2u | | y^2-6y=-91 | | 5x+3x+20=140 | | 9m-5-2m= | | 8+18n= | | 3y+y-16=145 | | 8n+4=-52 | | Y-16+3y=145 | | -6(y+7)=-3y-45 | | 4y+14=13-y | | (3z-2)2-8(3z-2)=20 | | M(n-7)= | | -2u+46=-6(u-7) | | T(t+9)= | | An=(n-1)2+3 | | (x^2-y^2)*dy-x*y*dx=0 | | 4(2f-1)= | | 2(u+9)=-8u-32 |

Equations solver categories